2021
DOI: 10.1002/jssc.202100398
|View full text |Cite
|
Sign up to set email alerts
|

Separation and determination of 3‐hydroxyaspartate by online concentration capillary electrophoresis/laser‐induced fluorescence with microwave‐assisted derivatization

Abstract: A chiral analytical method was proposed based on capillary electrophoresis with laser-induced fluorescence detection coupled with microwave-assisted derivatization for the simultaneous baseline separation and sensitive detection of four stereoisomers of 3-hydroxyaspartate. The derivatization reaction of 3hydroxyaspartate with 4-chloro-7-nitrobenzo-2-oxa-1,3-diazole was greatly accelerated by microwave irradiation. Under the optimized conditions, the derivatization yield was increased by 20% and the derivatizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This rate‐limiting step significantly reduces the analytical throughput. On the contrary, as reported in many papers [32, 33], MAD can significantly increase derivatization efficiency and reduce derivatization time, in the way that the analytes and derivatization reagent absorb microwave radiation and dielectric heating, directly through the dipole rotation and ion conduction between molecules [34]. Existing studies have confirmed that this auxiliary derivatization effect can be achieved by ordinary household microwave ovens, without the need for microwave devices with temperature control functions [35].…”
Section: Resultsmentioning
confidence: 99%
“…This rate‐limiting step significantly reduces the analytical throughput. On the contrary, as reported in many papers [32, 33], MAD can significantly increase derivatization efficiency and reduce derivatization time, in the way that the analytes and derivatization reagent absorb microwave radiation and dielectric heating, directly through the dipole rotation and ion conduction between molecules [34]. Existing studies have confirmed that this auxiliary derivatization effect can be achieved by ordinary household microwave ovens, without the need for microwave devices with temperature control functions [35].…”
Section: Resultsmentioning
confidence: 99%
“…CDs are non‐toxic to human health, have good water solubility, and are easily scaled up, and some papers report systems using native CDs as chiral selectors (α‐CD, β‐CD, and γ‐CD). The specialized literature reports the use of pure CDs for CE (especially the β‐CD, as is presented in Table 1 [56–96]). Initially, native CDs are preferred for chiral separation to obtain reproducible results (especially for the β‐CD) and to study aspects of the selector‐analyte interactions.…”
Section: Electrophoretic Methods For Enantioseparationmentioning
confidence: 99%
“…HDMS‐β‐CD is commonly used in methanolic and aqueous BGE for CE, such as for the enantiomeric separation of acebutolol (antihypertensive drug) [85]. TM‐β‐CD was satisfactorily applied to determine the enantiomers of 3‐hydroxyaspartate in urine and for six phenoxy acid herbicides [84, 95]. In addition to HDAS‐β‐CD, another ‐CD that has acetyl groups at positions C2 and C3 is oktakis‐(2,3‐diacetyl‐6‐sulfo)‐γ‐CD (ODAS‐γ‐CD), which has eight residues of glucopyranose units instead of seven [77].…”
Section: Electrophoretic Methods For Enantioseparationmentioning
confidence: 99%
“…Generally speaking, and among different protocols that can be applied to improve the preconcentration or separation of target analytes, perhaps the most common ones are off-line (also described as pre-column). These methods are generally manually performed by allowing researchers to control a wide range of conditions [523], including heating the sample and have been applied toward the analysis of acrylamide [524], mono-and oligosaccharides [525], sialylated N-glycan linkage isomers [526], 3-hydroxyaspartate [527], or acidic metabolites [528]. Off-line approaches have also allowed taking some advantage of advanced oxidation methods (combining H 2 O 2 and UV light) to follow the degradation of pharmaceuticals [529] or to convert alcohols into the corresponding acids, thus facilitating their separation by CE [350,530].…”
Section: Derivatizationmentioning
confidence: 99%